Müli, Loui, Rüfi.: Eine Untersuchung zur historischen Lautlehre im Berndeutschen anhand von Ortsnamen - Kistler, Simon (Linguistik Online, 2019)
Based on the material of the toponomastic dictionary of the Canton of Bern, or Ortsnamenbuch des Kantons Bern (BENB), this article first aims to describe how the final -i in today’s Swiss German dialects, as in müli ‘mill’, is represented in sources from the medieval era until the sixteenth century. It appears that the classical Middle High German -e grapheme is hardly found in our data, while -i is used throughout this entire period and beyond. However, it is shown that this becomes more complex whith respect to noun composition.Moreover, the historical relation between the short and long Swiss German forms loui – louene ‘avalanche’ and rüfi – rufene ‘landslide’ is discussed.